CONCILIATION ISSUES IN THE FIELD OF INTERNATIONAL INVESTMENT ARBITRATION (World Bulletin of Management and Law, 2024)
This article covers the issues of conciliation in the field of International Investment Arbitration, its definition and peaceful resolution of disputes of an international scope through the participation of the parties and a third party